Red Blood Cell Alloimmunization in Sickle Cell Disease Patients in Jeddah, Saudi Arabia: A Pilot Study. - Abdulrahman S. Alboog,; Taher M. Tayeb,; Mohammed O. Alsager,; Salwa A. AlNajjar,; Ghazi A. Damanhouri,; Jummanah S. Jarullah,; Salwa I. Hindawi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The treatment of patients with sickle cell disease frequently requires transfusion of red blood cells. Complications due to alloimmunization of red blood cells antigen remain a major risk as a post transfusion effect. The objective of this study is to determine the frequency of red cell alloimmunization in Jeddah, Saudi Arabia. A retrospective cross-section study of sickle cell disease patients at King Abdulaziz University Hospital between 2012 and 2013 was performed. Demographic characteristics and transfusion history was recorded. Blood samples were analyzed for alloimmunization using immunohematological technique. A total of 234 sickle cell patients were analyzed, of which 30 (12.8%) showed alloantibodies. A total of 43 alloantibodies were found out of which 28 belonged to Rh group, eight belonged to Kell while three belonged to MNS group. Demographic and transfusion characteristics were analyzed between alloimmunized and nonalloimmunized sickle cell disease patients. The rate of alloimmunization in Jeddah, Saudi Arabia was 12.8%. There was significant difference observed between alloantibodies detection between transfused patients compared to non-transfused patients. The consequences of red blood cell alloimmunization are highly significant and therefore immune hematological testing is highly recommended.